2019
DOI: 10.1002/bsl.2434
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the relationship among indicators for lone actor terrorist attacks: Multidimensional scaling and the TRAP‐18

Abstract: This validation study analyses data from a sample of North American terrorist attackers (n = 33) and non‐attackers (n = 23) through the lens of the Terrorist Radicalization Assessment Protocol (TRAP‐18; Meloy, 2017) utilizing a multivariate statistical approach – multidimensional scaling – to visualize potential clustering (co‐occurrence) of risk factors. Rarely done in terrorism research, the results plotted in two‐dimensional space show the clustering and co‐occurrence of most of the eight proximal warning b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 65 publications
(97 reference statements)
1
37
2
Order By: Relevance
“…The same findings were mirrored when terrorist attackers were compared to POCs investigated as being a potential terrorist, but who were threat managed for two years without an incident (Goodwill & Meloy, 2019; Meloy et al, 2019). As with the school shooters, identifying with previous attackers was more common in terrorist attackers, but there was not a difference in leakage between the two groups (Meloy et al, 2019).…”
Section: Comparing Persons Of Concern To Attackersmentioning
confidence: 65%
“…The same findings were mirrored when terrorist attackers were compared to POCs investigated as being a potential terrorist, but who were threat managed for two years without an incident (Goodwill & Meloy, 2019; Meloy et al, 2019). As with the school shooters, identifying with previous attackers was more common in terrorist attackers, but there was not a difference in leakage between the two groups (Meloy et al, 2019).…”
Section: Comparing Persons Of Concern To Attackersmentioning
confidence: 65%
“…and emotion," and "creativity and innovation" also occurred more frequently among the individual perpetrators, whereas mental disorder was registered less frequently (Meloy et al, 2019). In one of the latest studies Goodwill and Meloy (2019) were able to validate this theoretical model empirically on a database consisting of North American terrorist attackers and nonattackers. The authors showed in a multidimensional scaling study that proximal warning behaviors and distal characteristics differentially cluster.…”
Section: Studies On the Scientific Quality Of Trap-18mentioning
confidence: 88%
“…Conspiracy theories, religious fervor, or political ideology can grow rapidly, as the user sees more content without counterbalancing information, a partial result in contemporary times of social media algorithms deciding what the viewer should see next according to his or her interests or “likes.” This process of fixating on ideas may later coalesce into a self‐identity or identification. Recent research suggests that such evolution from fixation to identification may be an indicator of mobilization for violence among lone actor terrorists (Challacombe & Lucas, 2018; Goodwill & Meloy, 2019; Meloy et al, 2019). Likewise, over time, individuals with an ED change their diets so radically that cognitive shortcuts allow them to act without thinking each time they encounter food.…”
Section: Extreme Overvalued Beliefmentioning
confidence: 99%
“…Several clinical scales have been developed for obsessive‐compulsive disorder (OCD) screening and tracking. The Yale–Brown Obsessive Compulsive Scale (Goodman et al, 1989a, 1989b) is a clinically useful instrument for measuring OCD severity in adults, and has been used to evaluate efficacy for most of the available pharmacological treatments. However, there are still questions concerning the demarcation between obsessions as a symptom and schizophrenia‐spectrum psychopathology (Rasmussen, Nordgaard, & Parnas, 2019; Tolin, Abramowitz, Kozak, & Foa, 2001), particularly given the longitudinal relationship between a diagnosis of OCD and subsequent risk for schizophrenia (Meier et al, 2014).…”
Section: Obsessionmentioning
confidence: 99%